Лін-технології як імперативи елітарної освіти - Іванова, Оксана Станіславівна; Іванова, О. С.; Ivanova, Oksana S.; Єрмакова, Світлана Станіславівна (My University, 2022)
The article proposes to consider the possibilities of lean production technologies (lin-technologies) in educational organizations. The authors conclude that the use of lean production can achieve high results in solving a number of important tasks and provide a favorable innovation environment for the creation and implementation of innovative projects that are a priority in modern education.
Єрмакова С. С., Іванова, О. С. Лін-технології як імперативи елітарної освіти World Science. 2020. Vol.2, №4(56). Р. 31-36. https://doi.org/10.31435/rsglobal_ws/30042020/7036
Keywords: education; lean production; lin-technologies